Graph Passing in Graph Transformation - Ghamarian, Amir Hossein; Rensink, Arend (Electronic Communications of the EASST, 2012)
Graph transformation works under the whole world assumption. Therefore, in realistic systems, both the individual graphs and the set of all such graphs can grow very large. In reactive formalisms such as process algebra, on the other hand, each system is split into smaller components which continually interact; the interactions pass information such as names or locations between components. The state spaces for the separate components are typically much smaller, and much efficiency can be gained by analysing system behaviour on this level. In this paper we present a framework for compositional graph transformation inspired by name-passing calculi, in which (knowledge about) subgraphs can be passed between components. Essentially, we define graph-passing (reactive) component rules and their composition into traditional (reductive) whole-world rules. This extends previous work in which a simpler form of composition was proposed. The main result is a soundness and completeness result for the composition, showing that the transformations induced by the component rules and their whole-world counterparts are equivalent.